THE INFLUENCE OF THE PROBLEM-BASED LEARNING MODEL WITH PORTFOLIO ASSESSMENT OF SCIENTIFIC WRITING ABILITY BY STUDENTS’ COGNITIVE STYLE CONTROL - Tnunay, Paulus (Journal of Language, Education, Literature, and Culture, 2024)
This research aims to determine the Influence of the Problem-Based Learning Model (PBM) with portfolio assessment on the ability to write scientific writing with variable cognitive style. The study employs an experiment with a posttest-only control group design. The sample is 66 students; it is taken randomly based on class. The research instrument is a test (rubric) of work performance and cognitive style. It is analyzed in one-way ANOVA. This research finds that 1) H1 is accepted because Fcount 22,964 (0,00) <0,05. It means there is a difference in the capability in scientific writing between the students who join the PBM model with portfolio assessment compared to those who join the conventional learning model; 2) H1 is accepted because Fcount 6,756 (0,012) <0,05. It means that after co-variable cognitive is controlled, there is a difference in scientific writing ability for those students that join the PBM Model with portfolio assessment compared with the students that join the conventional learning model; 3) H1 is accepted because Fcount 27,512 (0,000) <0,05. It means that covariable cognitive style significantly contributes to the capability in scientific writing at 30,1%. The rest is 69,9, which is contributed to another variables beyond this study